Construction Industry in Ukraine: Transformations and Prospects in the Context of Martial Law and Postwar Reconstruction - Ivanova, H. P.; Olishevska, V. Ye.; Hapieiev, S. M.; Olishevska, S. O. (Science and Transport Progress, 2024)
Purpose. Military actions have caused serious changes in the economic sphere in all regions of the country. The construction industry is also experiencing major transformations and challenges. The main purpose of the study is to analyze current trends in the construction market of Ukraine, its features and future in the context of martial law and post-war reconstruction. Methodology. The full-scale invasion led to the near collapse of the construction industry, most Ukrainian enterprises were forced to suspend or limit production, and some reoriented to the needs of the Armed Forces. Many companies in the South and East of the country were in the area of active hostilities or under temporary occupation, as were logistics elements and suppliers of raw materials and components. Damage to the engineering infrastructure also had a negative impact on the production of construction products. Most of the raw materials and construction materials have to be imported, but the volume of imports is also limited, as the port infrastructure is practically non-existent. During the martial law period, the government adopted a number of decrees to facilitate the import of certain goods, but many construction materials are still not on the list. Import substitution and logistics restructuring are also taking place after the abandonment of goods from unfriendly countries that previously dominated such segments as the glass wool, bitumen, and other markets. The experience of other countries in protecting construction facilities from destruction during military operations is considered. Findings. The article analyzes the state of the domestic market and the problems of imports of building materials; staffing of the construction industry; changes in the structure and volume of demand in the construction and real estate sectors; changes in urban planning legislation, as well as the state of transport infrastructure; preparation for post-war reconstruction. Originality. A comprehensive analysis of the state of the construction industry of Ukraine during the armed aggression is carried out. The importance of introducing new safety and civil protection standards in the construction of construction projects, facilitating the issuance of permits, and developing the Unified State Electronic System in the field of construction is considered. Practical value. The article highlights the areas of construction and transport infrastructure that can be developed even during martial law, and considers the main problems of the construction industry in Ukraine.